MENINGKATKAN KEMAMPUAN MENGENAL LAMBANG BILANGAN MELALUI PERMAINAN STICK ANGKA PADA ANAK USIA 5-6 TAHUN DI TK PELITA HATI LUBUK TERENTANG KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Sukma jarnita; Mahdum '; Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: based on field observations of the numeracy skill of students is still low and teachers are still teaching methods that dominate and not varied. So that need the right learning methods with number stick games. The study aim to determine skill to identify numeracy with playing numer stick to children ages 5-6 years tk pelita hati lubuk terentang kecamatan gunung toar kabupaten kuantan singingi and to determine the learning methods with playing number stick games to children ages 5-6 years tk pelita hati lubuk terentang kecamatan gunung toar kabupaten kuantan singingi.  The sample used in this study are 16 children. This study perform by writer with take the place at taman kanak kanak pelita hati lubuk terentang kecamatan gunung toar. The time of this study will do at semester II study years 2015/2016, at april-july 2016. The kind of study is action class study. By the analitic study data persiclus showidentify the device of number with used number stick show incease. From the study receive before siclus that is point 28.1 became 40.6 at suclis I that is increase 44% and become 64 at siclus 2 that is increase 58%